IMPLEMENTASI METODE MOORA (MULTI-OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS) DALAM PEMILIHAN PROGRAM STUDI DI PERGURUAN TINGGI KOTA SEMARANG - Christian Thaddeus Hendratama; Setyawan Wibisono (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
In determining the choice of the right study program and college to continue education for the community and high school or vocational high school students it is very important. There are factors that influence the selection process, namely interests, talents, costs, accreditation and the quality of existing teachers. By applying the Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) method, these factors can be used as criteria in determining the best available recommendations. Various stages of the MOORA calculation process as well as minimum and very simple calculations are implemented into the Decision Support System (DSS) so that the selection is faster and more precise. This study takes the variables of the study program of informatics engineering and information systems at private universities in the city of Semarang as an alternative choice. The results obtained from the calculation of the MOORA method in this study indicate alternative A9 as a recommendation for the best study program choice at universities in the city of Semarang. Abstract: In determining the choice of the right study program and college to continue education for the community and high school or vocational high school students it is very important. There are factors that influence the selection process, namely interests, talents, costs, accreditation and the quality of existing teachers. By applying the Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) method, these factors can be used as criteria in determining the best available recommendations. Various stages of the MOORA calculation process as well as minimum and very simple calculations are implemented into the Decision Support System (DSS) so that the selection is faster and more precise. This study takes the variables of the study program of informatics engineering and information systems at private universities in the city of Semarang as an alternative choice. The results obtained from the calculation of the MOORA method in this study indicate alternative A9 as a recommendation for the best study program choice at universities in the city of Semarang.